Historical graffiti as the voice of the disadvantaged - Ozcáriz Gil, Pablo (Huarte de San Juan. Geografía e Historia, 2024)
An introduction to the Full Issue
Keywords: Historical graffiti; Historical sources; disadvantaged; marginal epigraphy; diachronic studies